Re-evaluation of mouse models of endometriosis for pathological and immunological research - He, Ying; Liang, Bo; Hung, Sze Wan; Zhang, Ruizhe; Xu, Hui; Chung, Jacqueline Pui Wah; Wang, Chi Chiu (Frontiers in Immunology, 2022)
Endometriosis is an estrogen-dependent gynecological disease with chronic pelvic inflammation. In order to study the pathophysiology of endometriosis and examine the therapeutic effects of new pharmaceuticals for endometriosis treatment, different animal models had been developed in the last two decades, especially mouse models. However, no study evaluated the effects of various modeling approaches on pathology and immunology in endometriosis. This study aimed to compare endometriotic lesion development and immune profiles under different methods of establishing endometriosis models in mice, including estrus synchronization (ovariectomy with estrogen supplement versus male urine-soaked transfer bedding), endometrium preparations (whole uterus including endometrium and myometrium fragments versus solely endometrium fragments), and surgical transplantation (subcutaneous transplantation versus intraperitoneal injection). Our results showed that lesion growth under estrus synchronization by ovariectomy with estrogen supplement had a higher success rate and more proliferative endometrium, apart from higher body weight gain. Immune responses in peripheral blood were similar in the whole uterus and solely endometrium fragments and in intraperitoneal injection and subcutaneous transplantation, but a more innate immune response in the peritoneal microenvironment was found in solely endometrium fragments and intraperitoneal injection than counterparts. In conclusion, different endometriosis modeling methods result in different pathological and immunological features. Ovariectomy with estrogen supplement, solely endometrium fragments, and intraperitoneal injection are more suitable for both pathological and immunological studies of endometriosis in mice, which are important for mechanistic studies and immunotherapy development.